Perioperative Anesthesia Management for a Patient Presented with Acute Cardiopulmonary Compromise Secondary to a Complicating Retropharyngeal Abscess Extending to the Mediastinum. A Rare Case Report - Kelbesa Olika M; Teku Ayano G; Ilala TT (Open Access Surgery, 2022)
Megersa Kelbesa Olika,1 Gudeta Teku Ayano,2 Tajera Tageza Ilala2 1Department of Anesthesia, Institute of Health, College of Public Health and Medical Science, Jimma University, Jimma, Oromia, Ethiopia; 2Department of Anesthesia, Faculty of Medicine, College of Medicine and Health Science, Hawassa University, Hawassa, Sidama, EthiopiaCorrespondence: Tajera Tageza Ilala, Department of Anesthesia, Faculty of Medicine, College of Medicine and Health Science, Hawassa University, Hawassa, Sidama, Ethiopia, Email tajeratageza@gmail.comBackground: A retropharyngeal abscess is a bacterial infection of the back of the throat. It rarely results in deadly complications such as mediastinitis and thoracic empyema from deep neck infections involving soft tissues of the face, arising from oropharyngeal infections, particularly dental caries. Thus, complicating retropharyngeal abscess extending to mediastinitis poses an increased risk of high mortality rate as a result of its significant invasive potential and the fact that the recognition and diagnosis must be made early, as this is usually delayed. Complicating retropharyngeal abscess increases airway compromise and difficult airway management during anesthesia. We present a 40-year-old, male patient who transferred from another primary hospital to our institution’s surgical emergency outpatient department with a complaint of neck swelling of 10 days secondary to tooth extraction. He had a complaint of dull-itching pain, localized initially to the submandibular area and subsequently involving the oropharyngeal, neck, and descending to the chest and mediastinum. He was diagnosed with a complicated retropharyngeal abscess extending to the mediastinum (mediastinitis) and thoracic empyema as a complication of odontogenic infection in origin. Besides intravenous antimicrobial therapy, deep neck incision and drainage, and thoracotomy was done under general anesthesia. After adequate venous access and the patient positioned in head-up position, premedication was given. General anesthesia with an endotracheal tube was provided with a ready tracheostomy set. Inhalational induction was conducted and laryngoscopy was performed after the adequate depth of anesthesia was achieved. We experienced anticipated difficult intubation after induction. After multiple attempts, the tracheal tube was placed correctly by using a bougie. Halothane was used for maintenance anesthesia with intermediate-acting muscle relaxant under controlled ventilation.Conclusion: On top of a detailed review of the patient’s history, physical examination, laboratory investigations, and imaging profiles; early recognition of the airway compromise from the complicated retropharyngeal abscess, and proper readiness to manage potentially challenging airway compromise, and difficult airway management during the perioperative period.Keywords: anesthesia, anesthesia management, dental infections, incision and debridement, Ludwig angina, mediastinitis, mediastinal abscess, retropharyngeal abscess, airway management, retropharyngeal abscess